Acceleration of Digitalization of the Health Sector in Surakarta City - Nella Tri Surya; Anggi Putri Aria Gita; Frieda Ani Noor; Agustina Pujilestari (PROMOTOR, 2023)
Rapid technological advances encourage humans to use it in helping daily life activities, one of which is in the world of health, Digitalization is the process of transferring form from printed to digital form, but there are several obstacles in the operation of several PIS PIK applications used by puskesmas to collect health data, especially at the Nscratch Health Center in Surakata city and the lowest IKS achievement data (0.429) is at the Nscratch Health Center. This study aims to find out how successful the Acceleration of Digitalization of the Health Sector in Surakarta City is. This type of research uses a qualitative method and is carried out by in-depth interviews method to health workers who use applications at Puskesmas. The sampling technique in this study is Purposive Sampling. The results of the research that have been obtained are the role of humans or health workers in the implementation of several applications used in puskesmas. Puskesmas Nscratch still has miscommunication between officers or users because some officers are still busy with other tasks so they transfer their duties to other officers to enter data into the application, causing data input into the application to be hampered not by in the field. Organizational structure and environment to the role of health workers in the implementation of the Application.